2011
DOI: 10.1002/ar.21409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduced c‐Kit Signaling on Bone Marrow Adiposity

Abstract: c-Kit (CD117) is required for normal differentiation of osteoblasts from bone marrow stromal cells and for normal bone formation. Osteoblasts and adipocytes originate from a common progenitor cell, and a reciprocal relationship in differentiation of the two lineages is often observed. Therefore, the effects of abnormal c-kit signaling on bone marrow adiposity and adipocyte precursor pool size were evaluated in mouse strains with loss of function mutations in kit receptor or kit ligand. Additionally, to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Secreted kit ligand binds to and activates kit receptor but is unable to duplicate all of the actions of the membrane-associated ligand [51, 54, 55]. As a consequence, kit Sl/Sl-d mice are sterile, anemic, osteopenic, have elevated osteoclast perimeter and have no marrow adipocytes [24]. Thus, activation of kit signaling through kit receptor by membrane-associated kit ligand appears necessary for differentiation of a variety of marrow-derived cells, including adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secreted kit ligand binds to and activates kit receptor but is unable to duplicate all of the actions of the membrane-associated ligand [51, 54, 55]. As a consequence, kit Sl/Sl-d mice are sterile, anemic, osteopenic, have elevated osteoclast perimeter and have no marrow adipocytes [24]. Thus, activation of kit signaling through kit receptor by membrane-associated kit ligand appears necessary for differentiation of a variety of marrow-derived cells, including adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of a strong inverse association between bone marrow fat and bone mass, it has proven difficult to directly test the hypothesis that excess fat accumulation in bone marrow is responsible for ovx-induced osteopenia. In this regard, we recently reported that kit receptor-deficient kit W/W-v mice have no bone marrow adipocytes [24] but are able to produce osteoblasts and osteoclasts. We therefore reasoned that if bone marrow adipose tissue contributes to the detrimental skeletal effects of estrogen deficiency, kit W/W-v mice would be resistant to ovx-induced osteopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms are not completely understood but c-kit signaling has been suggested to couple MSC and HSC differentiation in BM. In this regard, loss of function mutations in the c-kit receptor and membrane-bound kit-ligand result in certain hematopoietic defects such as anemia and mast cell depletion, and absence of BMA in long bones and lumbar vertebrae [61].…”
Section: Bma Metabolic Functionmentioning
confidence: 99%
“…Loss of function mutations in c-kit receptor and kit-ligand can result in anemia, mast cell deficiency, altered body composition, and skeletal abnormalities. Mutations leading to global reduction in c-kit receptor function (e.g., kit W/Wv ) and m-kit ligand function (e.g., kit Sl/Sld ) in mice also result in absence of MAT in long bones and lumbar vertebrae [65]. A deficiency in kit signaling in mice prevents ovariectomy-induced increase in MAT and accentuates bone loss in hindlimb-unloaded mice [66, 38].…”
Section: Role Of C-kit Signaling In Coupling Msc and Hsc Differentiatmentioning
confidence: 99%
“…Kit Sh/Sh mice have a mutation in a regulatory element leading to cell-specific loss of kit signaling. The mice are mast cell-deficient but in contrast to kit W/Wv and kit Sl/Sld are not anemic and have MAT, indicating that the absence of MAT is due to kit signaling insufficiency and not mast cell deficiency, per se [65]. Adoptive transfer of WT bone marrow into kit W/Wv mice was effective in replacing kit W/Wv HSCs with WT HSCs but, surprisingly, did not result in MAT infiltration [38].…”
Section: Role Of C-kit Signaling In Coupling Msc and Hsc Differentiatmentioning
confidence: 99%